Relações Estado-Sociedade e ações de governabilidade, governança e accountability como desafios contemporâneos à democracia no Brasil - CARVALHO, André Cutrim (União Atlântica de Pesquisadores, 2023)
The main objective of this article isto discuss the State-Society relationship and governability, governance and accountability actions as contemporary challenges to Brazilian democracy. To achieve this objective, the article usedexploratory-qualitative research methodology. The main conclusion is that creating, disseminating and implementing improvements in the effectiveness of governability, governance and accountability strategies are essential for the maintenance of democracy and the strengthening developmentin Brazil. This is because the consolidation of democracy that achieves governability in Brazil must be thought of in direct connection with a true national project of development and reduction of socioeconomic inequalities. In fact, the democratic consolidation that achieves good governance and governance in Brazil, without deviations from planning or ideological rhetoric, permeates the need to improve its accountability. It is, therefore, a slow and gradual advance towards a more evolved society that is “aware” of what is important to improve democratically as a nation.